Modulation of receptor for advanced glycation end products signal transduction pathway as therapeutic option for malaria therapy - Chuah, Yaw Kuang (2015)
Receptor for advanced glycation endproducts (RAGE), an important receptor in the regulation of innate immune response, has been associated with many inflammatory related diseases such as septicaemia, rheumatoid arthritis, and arteriosclerosis. Malaria is also considered as an inflammatory disease involving excessive inflammatory response towards parasite invasion and severe systemic inflammation occurred during the infection has been closely linked to morbidity and mortality of the disease. However, RAGE involvement during malaria infection has yet to be revealed. In this study, the role and involvement of RAGE during malaria infection was investigated and the effects of modulating RAGE on the course of the infection, the release of major inflammatory cytokines and the histopathological consequences in major affected organs during malaria were evaluated. Plasmodium berghei (P. berghei) ANKA infection in male ICR mice was used as a model for malaria infection. The mice were inoculated intraperitoneally with 2 x 107 parasite-infected red blood cells (PRBCs) whereas the control mice received an equivalent dilution of normal RBCs. The plasma levels of RAGE in malarial mice were measured by ELISA. Results showed that RAGE was upregulated during malaria especially at the late critical phase of infection and there is a positive correlation between RAGE concentration and parasitaemia development suggesting that RAGE could be one of the important factors in mediating the severity of the infection. Modulation of RAGE expression was carried out by treatment of malarial mice with recombinant mouse RAGE Fc chimera (rmRAGE/Fc Chimera) or mouse RAGE polyclonal antibody (mRAGE/pAb) intravenously. Both treatments did not affect the parasitaemia development during malaria infection. Blocking RAGE signaling pathway during the infection period significantly result in an elevation in the plasma levels of interleukin (IL)-4 and IL-17A, a further increase in IL-10 and IL-2 plasma levels, and reduced secretion of interferon (IFN)-γ in the plasma. But no effect on the release of tumor necrosis factor (TNF)-α and IL-6 was observed. Histopathological examination was performed on five major organs affected during malaria including liver, spleen,brain, kidney, and lung. The results showed that modulation of RAGE expression improve the histopathological conditions of malaria to some degree. Both treatment groups showed an overall better outcome in histopathological conditions of all five organs despite the lack of effect on the course of the parasitaemia. In conclusion, the findings from this study showed that RAGE is involved during immune response towards malaria infection and blocking of RAGE may prove beneficial by reducing tissue injury to a lesser degree. Hence, this suggests the potential of RAGE as an immunotherapeutic target in malaria, in which the host may benefit from its inhibition.